Wide Complexes Tachycardia in Xenobiotic Poisoning - Uzelac, Bojana; Đikić, Marina (Halo 194 Scientific Journal of Emergency Medicine, 2020)
Wide complex tachycardias (WCT) represent an electrocardiographic record rate over 100/minute and QRS complex width over 120ms. The classic division of WCT involves ventricular tachycardia and supraventricular aberrantly conducted, but may also caused by metabolic and/or toxic agents. Xenobiotic is a chemical substance presented in an organism, but not produced or expected to be present in it. These are also substances present in the body at a much higher concentration than usual. For humans, drugs are also xenobiotics. One group of xenobiotic poisoning disorders is based on the cardiomyocyte membrane's sodium channels blockage, which are responsible for initial, 0th phase of the action potential. Certain drug groups may induce WCT as a consequence of impaired repolarization and prolongation of QTc intervals. Treatment of WCT within xenobiotic poisoning depends on the type of tachycardia and underlying disorder. Early recognition and initiation of adequate therapy are invaluable for a favorable patient outcome.
Keywords: broad complex tachycardia, WCT, xenobiotics, poisoning